An implementation intention strategy can improve prospective memory in older adults with very mild Alzheimer's disease. (20th May 2015) - Lee, Ji Hae; Shelton, Jill T.; Scullin, Michael K.; McDaniel, Mark A.
Abstract : Objectives: This study tested whether (1) very mild Alzheimer's disease (AD) is associated with impaired prospective memory (PM) for tasks that are supported by either spontaneous retrieval (focal PM) or strategic monitoring (non‐focal PM) and (2) implementation intention (II) encoding could improve PM performance in very mild AD. Design: Thirty‐eight healthy older adults and 34 with very mild AD were randomly assigned to perform two PM tasks in either the standard or the II encoding condition. Method: All participants performed blocks of category decision in which they were asked to respond to a focal PM target (e.g., the word 'orange') and a non‐focal PM target (e.g., words that begin with the letter 'o'). Half of the participants encoded PM instructions in the standard manner, while the other half had a stronger encoding by forming IIs. PM accuracy and category decision accuracy and reaction times were measured. Results: Participants with very mild AD showed deficits in both focal and non‐focal PM performance compared to the healthy controls, reflecting deficits in both spontaneous retrieval and strategic monitoring. Participants with very mild AD in the II encoding condition showed better focal PM performance relative to those in the standard encoding condition. Conclusions: Deficits in both focal and non‐focal PM are associated with very mild AD and IIs may be a helpful behavioural intervention for the focal PM deficits. Practitioner points: Multiple deficits in PM are observable in very mild AD. Implementation intentions may enhance focal PM in very mild AD. Future research using larger samples is needed to better understand the effect of II on non‐focal PM tasks in healthy older adults and those with very mild AD. The use of simple laboratory PM tasks may limit the generality of our findings. Future research is needed to investigate whether IIs improve PM over a range of more realistic tasks.